Development of Student Worksheets Based on Critical Thinking Biotechnology Materials for Third Grade (IX Class) of Junior High School - Sinaga, Hazria; Anas, Nirwana (Universitas Labuhanbatu, 2022)
Critical thinking is a skill that needs to be developed. LAPD is an alternative teaching material that can be used in learning activities with the aim of improving students' critical thinking skills. The purpose of this research is to produce teaching materials in the form of LKPD oriented to critical thinking on biotechnology materials which are declared feasible, practical and effective. The method applied is R&D with a 4D development model. LKPD validation by media experts, LKPD material and practicality by field practitioners. The LKPD test was carried out in third grade (IX class) of Junior High School (IX A) SMP Negeri 1 Barus with 34 students, to see the effectiveness of the pre-test and post-test tests along with student response questionnaires. The results of the validation are in the very feasible category with a percentage of 84%, the practicality of the LKPD with a percentage of 94% which is included in the very practical category. The effectiveness of LKPD is measured by the N-Gain test, the average pre-test and post-test of students with a score of 0.6 in the medium category, meaning that student scores have increased and student questionnaire responses are 82% in the very good category. Therefore, the developed LKPD is categorized as very feasible, practical and effective to use